English Students’ Attitudes towards English Language Teaching and Learning at IAIN Padangsidimpuan - Ida Royani; T. Silvana Sinar (LINGUISTIK TERAPAN, 2016)
This study investigated the English students’ attitudes of IAIN Padangsidimpuan towards both English language teaching in terms of (a) language-centered, (b) learner-centered, and (c) learning-centered method; and learning English in terms of scales (a) attitudes toward long-term English learning, (b) interest in culture and communication, (c) perception about studying in school context, (d) images associated with English, (e) English learning activities, (f) exposure to English outside school, (g) self-rated four English skills, (h) self-reported academic English grade, and (i) identification of English role models. The data were obtained by questionnaire and interview from 10 selected students in which 4 male and 6 female students in 7th semester and were analyzed by steps provided by Gay, L.R and Airasian (1996). The result showed:  first, English students’ attitudes towards English language teaching had been found highly onlearning-centered method, followed by learner-centered method in second range, and almost negative view in language-centered method.Second, English students’ attitudes towards English language learningwere positivein scales; long-term English learning, interest in communication, and images associated with English.  Third, role of students’ gender on English language learning were not found. Reasons for this statement are (i) status of English as international language and (ii) equalization of getting education for male and female. Keywords: attitude, language teaching, language learning, and gender